The Role of Lifestyle Factors in Controlling Blood Pressure among Hypertensive Patients in Two Health Facilities in Urban Ghana: A Cross-Sectional Study - Emefa Modey Amoah; Darlene Esinam Okai; Adom Manu; Amos Laar; Joseph Akamah; Kwasi Torpey (International Journal of Hypertension)
Introduction. Despite efforts to combat hypertension by pharmacotherapy, hypertension control rates remain low. Lifestyle modifications of individuals diagnosed with hypertension have prospects for the prevention and control of hypertension. This study assessed the effect of modifiable lifestyle factors on blood pressure control among adults in urban Accra. Methods. In this cross-sectional study, 360 diagnosed hypertensive patients who were ≥18 years old, selected from two secondary-level referral hospitals in the Greater Accra Region, were interviewed. Demographic information, diet components, and exercise assessments as well as blood pressure measurements were taken. Chi-squared tests and binomial logistic regression were used to determine the association between demographic and lifestyle factors with blood pressure control. Area under the receiver-operator curves (AUROC) was used to identify lifestyle factors predicting optimal blood pressure control among patients diagnosed with hypertension. Results. Approximately 54.2% of participants had no knowledge of either causes or complications of hypertension. Similarly, 52.5% of patients that had not achieved blood pressure control lacked knowledge of causes or complications of hypertension. Longer time since diagnosis of 2–5 years (AOR = 0.08 (95% CI: 0.01–0.47)) and 6–10 years (AOR = 0.08 (95% CI: 0.01–0.50)) and diets, mainly composed of meat (AOR = 0.13 (95% CI: 0.02–0.70)) and starch (AOR = 0.14 (95% CI: 0.03–0.79)), predicted poor blood pressure control compared to patients diagnosed within a year and diets without meat and starch as main components, respectively. Additionally, engaging in some physical activity of 30 minutes to one hour (AOR = 5.64 (95% CI: 2.08–15.32)) and more than an hour (AOR = 11.38, 95% CI: 2.01–64.47)) predicted blood pressure control. Conclusion. The study concludes that increased physical activity, abstaining from alcohol and smoking, increased intake of fruits and vegetables, and reduced intake of carbohydrates, meat, and fat have a positive influence on blood pressure control. Lifestyle modifying factors have a key role in complementing pharmacotherapy in hypertension control.